(untitled) (International Journal of Engineering and Computer Science, 2016)
Non Homogeneous Poisson process models with expected number of faults detected in given testing time are proposed in the literature. These models show either constant, monotonic increasing or monotonic decreasing failure occurrence rate per fault. In this article we propose a software reliability model in which the distribution of time between two failures assumed to be log logistic distribution. The model can capture increasing/decreasing nature of failure rate. The parameters of the model are estimated using maximum likelihood method. A simulation study and real data are used to verify the model.